PERLINDUNGAN KONSUMEN DALAM PERBUATAN MELAWAN HUKUM PEMBELIAN DIAMOND GAME ONLINE MOBILE LEGENDS - Sulthan Muhammad Al Ghifari, (Fakultas Hukum Universitas Udayana, 2022)
The purpose of this study is to examine the legal certainty of online buying and selling transactions of Mobile Legends Bang-Bang diamonds through top-up stores, the legal position of Mobile Legends diamonds as digital commodities, and consumer protection in unlawful acts of buying and selling Mobile Legends Bang-Bang diamonds through top-up stores. This research uses normative judicial techniques, namely doctrinal legal research that uses document studies, literature studies, and secondary data consisting of primary, secondary, and tertiary legal sources. Mobile Legends diamond top-ups purchased through the top-up store fall under the realm of civil law. Diamond is a "digital commodity," which is a commodity in the form of goods used in online games that have monetary value and can be exchanged. Legal protection will create a balance between the positions, rights, and obligations of consumers and business actors.